2017
DOI: 10.1002/jcb.26460
|View full text |Cite
|
Sign up to set email alerts
|

BMP9/COX‐2 axial mediates high phosphate‐induced calcification in vascular smooth muscle cells via Wnt/β‐catenin pathway

Abstract: Vascular calcification is a notable risk factor for cardiovascular system. High phosphate can induce calcification in vascular smooth muscle cells (VSMCs), but the detail mechanism underlying this process remains unclear. In the present study, we determined the relationship between high phosphate and bone morphogenetic protein 9 (BMP9) in VSMCs, the effect of BMP9 on calcification in VSMCs and the effect of COX-2 on BMP9 induced calcification in VSMCs, as well as the possible mechanism underlying this biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Our study indicated that Wnt pathway was involved in CKD VC, which is consistent with previous studies . Addition of Wnt pathway inhibitor secreted frizzeled‐related protein 5 could inhibit high phosphate‐induced calcification of VSMCs .…”
Section: Disccusionsupporting
confidence: 92%
“…Our study indicated that Wnt pathway was involved in CKD VC, which is consistent with previous studies . Addition of Wnt pathway inhibitor secreted frizzeled‐related protein 5 could inhibit high phosphate‐induced calcification of VSMCs .…”
Section: Disccusionsupporting
confidence: 92%
“… Besides, Rong et al reported that BMP‐2 plays a crucial role both in calcium deposition in VSMCs and VC in CKD patients via a mechanism involving the Wnt/β‐catenin pathway . In addition, BMP‐9 was also been reported to induce VC through activating the Wnt/β‐catenin pathway . In contrast, Deng et al revealed secreted frizzled‐related protein 5 (SFRP5) attenuates high phosphate‐induced calcification in vascular smooth muscle cells by inhibiting the Wnt/β‐catenin pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Primary rat aortic VSMCs were employed for this study. The primary rat aortic VSMCs were extracted and cultured as described . Briefly, Male Sprague‐Dawley (SD) rats (150‐180 g, 10‐12 week) were ordered from the Laboratory Animal Center of Chongqing Medical University.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations